Dynamics of kerosene-based nanofluid in the core region of curved pipe surrounded by a peripheral region containing water-based nanofluid - H. Shahzad; Z. Abbas; M.Y. Rafiq (International Journal of Thermofluids)
This study investigates the flow dynamics and heat transfer characteristics of two immiscible nanofluids (kerosene-ZnO and water-Cu) flowing through a heated curved pipe under a constant axial pressure gradient, with applications in biomedical devices and industrial heat exchangers where curved geometries and multi-fluid systems are prevalent. The research addresses a critical gap in understanding how curvature-induced secondary flows and nanoparticle properties influence thermal performance in such configurations. By employing a perturbation method and non-dimensional analysis, we derived analytical solutions to the modified Navier-Stokes equations to examine the velocity and temperature distributions. Our analysis systematically varied key parameters, including curvature ratio, Reynolds number, and nanoparticle concentration to quantify their effects. The results demonstrate that increasing the curvature ratio to 0.1 enhances axial velocity near the outer wall by 15–25 % due to centrifugal forces, while higher Reynolds numbers above 50 intensify secondary flow vortices by 20 %, significantly improving fluid mixing. Notably, incorporating nanoparticles at 4 % concentration boosts heat transfer performance by 30–35 % compared to base fluids, attributed to enhanced thermal conductivity. Additionally, the temperature distribution shows a 15–20 % reduction near the walls relative to the core region, indicating efficient thermal gradient establishment. This work provides novel contributions as the first analytical solution for immiscible nanofluids in curved pipes and quantifies the previously unexplored synergistic effects of curvature and nanoparticles. These findings offer valuable insights for optimizing the design of compact heat exchangers and bioengineered systems, advancing beyond conventional single-fluid approaches in the literature.